Coseismic stress distribution along active structures and their influence on timedependent probability values. - Paradisopoulou, P.; Papadimitriou, E.; Mirek, J.; Karakostas, V. (Bulletin of the Geological Society of Greece, 2013)
Based on the fact that stress changes caused by the coseismic slip of strong events can be incorporated into quantitative earthquake probability estimates, the goal of this study is to estimate the probability of the next strong earthquake (M≥6.5) on a known fault segment in a future time interval (30 years). The probability depends on the calculation of ΔCFF and the estimate of the occurrence rate of a characteristic earthquake, conditioned to the elapsed time since the previous event. The Coulomb stress changes caused by previous earthquakes are computed and their influence are considered by the introduction of a permanent shift on the time elapsed since the previous earthquake or by a modification of the expected mean recurrence time. The occurrence rate is calculated, taking into account both permanent and temporary perturbations. The estimated probability values correspond to the probabilities along each fault segment with discretization of 1km, illustrating the probability distribution across the specific fault. In order to check whether the estimated probability vary with depth, all the estimations were performed for each fault at depths of 8, 10, 12 and 15 km.